2018
DOI: 10.1113/jp275911
|View full text |Cite
|
Sign up to set email alerts
|

Apparent calcium dependence of vesicle recruitment

Abstract: During sustained synaptic transmission, recruitment of new transmitter-filled vesicles to the release site counteracts vesicle depletion and thus synaptic depression. An elevated intracellular Ca concentration has been proposed to accelerate the rate of vesicle recruitment at many synapses. This conclusion is often based on the finding that increased intracellular Ca buffering slows the recovery from synaptic depression. However, the molecular mechanisms of the activity-dependent acceleration of vesicle recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…This is similar to the recent findings at cerebellar mossy fibre terminals (Ritzau‐Jost et al . ). The calyx of Held terminals have Ca‐sensitive and insensitive components of recovery (Wu & Borst, ; Sakaba & Neher, ; Lipstein et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is similar to the recent findings at cerebellar mossy fibre terminals (Ritzau‐Jost et al . ). The calyx of Held terminals have Ca‐sensitive and insensitive components of recovery (Wu & Borst, ; Sakaba & Neher, ; Lipstein et al .…”
Section: Discussionmentioning
confidence: 97%
“…For example, the modified serial model, which assumes that vesicles fuse from both the RRP and the RP (Wu & Borst, ; Ritzau‐Jost et al . ), could fit the data. Similarly, the parallel model, which assumes parallel vesicle recruitment to the RRP and the RP (and release from both pools), could fit the data (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Soon after the discovery of Ca 2+ ‐dependent recovery, Wu & Borst () showed that prolonged stimulation at the calyx of Held results in the release of two distinct pools of vesicles with differing kinetics of both release and replenishment They proposed a model with striking similarities to that of Ritzau‐Jost et al . (). Importantly, Ritzau‐Jost et al .…”
Section: Two Vesicle Pools: Fast and Slowmentioning
confidence: 97%
“…In this issue of The Journal of Physiology Ritzau‐Jost et al . () provide an elegant analysis and a new perspective on Ca 2+ ‐dependent recovery from depression, and suggest that – for at least one synapse – the phenomenon that has been observed may have little to do with vesicle replenishment.…”
Section: Two Vesicle Pools: Fast and Slowmentioning
confidence: 99%
See 1 more Smart Citation